INCREASING KADER KNOWLEDGE AND SKILLS IN THE DEVELOPMENT OF TODDLER FEEDING PRODUCTS BASED ON HIGH PROTEIN MULTIPURPOSE FLOUR PRODUCTS TO PREVENT TODDLER WASTING IN BULAK DISTRICT, SURABAYA CITY - Dr. Annis Catur Adi, Ir., M.Si; Mohammad Fahmi Rasyidi; Wizara Salisa; Fariani Syahrul; Santi Martini (Jurnal Layanan Masyarakat, 2023)
Wasting is a nutritional problem that is still the focus of attention in the management of health problems in infants and toddlers. The existence of the COVID-19 pandemic has hampered Posyandu service activities for toddlers, so that control over toddler waste has decreased. The role of cadres as the leading pillar in community service, especially with toddlers, is the main focus that needs to be put forward. Increasing the knowledge and skills of cadres is important to improving the quality of service to the community, especially toddlers. This community service aims to increase the role of posyandu cadres in an effort to reduce waste problems through increasing knowledge and developing MP-ASI innovations from high-protein multipurpose flour products. This activity consisted of two methods, namely, TOT (training of trainers) for cadres and mentoring toddler waste by posyandu cadres. Training activities for cadres consist of materials on wasting and prevention efforts as well as training on making MP-ASI based on high-protein multipurpose flour. This community service activity is carried out in the working area of ​​Bulak District with a focus on selected Posyandu with the target of wasting toddlers. The results of this community service activity can be seen in the increase in the knowledge of posyandu cadres in the Bulak District by 16.5% about the problem of toddler wasting. The improvement in the skills of cadres and mothers of toddlers in processing various kinds of toddler food menus based on high-protein multipurpose flour also looks quite good, as evidenced by the success in creating various types of food menus that are directly applied to toddlers. The conclusion in this community service activity is that counseling, training, and assistance provided can increase the knowledge and creativity of posyandu cadres and mothers of toddlers in creating MP-ASI based on high-protein multipurpose flour as an effort to combat wasting.